A review of karenia mikimotoi: Bloom events, physiology, toxicity and toxic mechanism - Li, Xiaodong; Yan, Tian; Yu, Rencheng; Zhou, Mingjiang (Harmful algae, 2019)
Karenia mikimotoi is a worldwide bloom-forming dinoflagellate in the genus Karenia. Blooms of this alga have been observed since the 1930s and have caused mass mortalities of fish, shellfish, and other invertebrates in the coastal waters of many countries, including Japan, Norway, Ireland, and New Zealand. This species has frequently bloomed in China, causing great financial losses (more than 2 billion yuan, Fujian Province, 2012). K. mikimotoi can adapt to various light, temperature, salinity, and nutrient conditions, which together with its complex life history, strong motility, and density-dependent allelopathy, allows it to form blooms that are lethal to almost all marine organisms. However, its toxicity differs between subspecies and some target-species-specific toxicity has also been recorded. Significant gill disorder is observed in affected fish, to which the massive fish kills are attributed, rather than to the hypoxia that occurs in the fading stage of a bloom. However, although this species is haemolytic and cytotoxic, and generates reactive oxygen species, none of the isolated toxins or lipophilic extracts have toxic effects as extreme as those of the intact algal cells. The toxic effects of K. mikimotoi are strongly related to contact with intact cells. Several reasonable hypotheses of how and why this species blooms and causes mass mortalities have been proposed, but further research is required.